Improving Soil Fertility Through Agricultural Waste Treatment in Subak Telun Ayah, Gianyar, Bali - Muliarta I Nengah; Desak Ketut Tristiana Sukmadewi Sukmadewi (Asian Journal of Community Services, 2023)
The community service carried out aims to increase the knowledge and understanding of farmers in the processing of agricultural waste, especially composting rice straw. Community service is also held to increase farmers' knowledge regarding the role of rice straw compost in improving soil fertility. The method used is socialization or counseling as a form of knowledge transfer to farmers. The socialization involved 20 members of the Subak Telun Ayah group, Gianyar Bali. The results show that due to limited knowledge of the benefits of rice straw for soil fertility, farmers tend to burn the agricultural waste produced. Farmers also do not believe in the benefits of compost so they prefer the use of inorganic fertilizers.